Factors Predicting Road Safety Behavior among Burapha University Staff and Students - Yingratanasuk, Tanongsak; Serikajornkicharoen, Pissamai; Yenjai, Pornthip (Journal of Health Science of Thailand, 2017)
A cross-sectional survey research which aims at determining factors related to road safety behavior among students and staff of Burapha University, Bang Saen, Chon Buri Province. The research instrument was constructed based on PRECEDE- PROCEED Framework: Educational Diagnosis. Data were collected from randomly selected 520 subjects during February 2012 – July 2013. Descriptive statistics in terms of numbers, percentages, and inferential statistics such as Pearson’s correlation and multiple regression analysis were utilized. The results revealed that more than 80% of Burapha University staff and students were neither a speeder nor drinking while on the road. Majority of them (63.3%) fastened seat belts; 37.1% did not use a mobile phone while driving or riding; and 32.3% wore helmet every time. University status, gender, income, and road accident knowledge and perceptions jointly predicted 11% of road safety behavior. Enabling and predisposing factors could not predict safety behavior in this study population. The authors suggested that promoting road safety behavior should be focused on the provision of correct knowledge regarding road accident prevention, especially among male students.